1997
DOI: 10.1021/bi971272q
|View full text |Cite
|
Sign up to set email alerts
|

Minor Groove-Directed and Intercalative Ligand−DNA Interactions in the Poisoning of Human DNA Topoisomerase I by Protoberberine Analogs

Abstract: Spectroscopic, calorimetric, DNA cleavage, electrophoretic, and computer modeling techniques have been employed to characterize the DNA binding and topoisomerase poisoning properties of three protoberberine analogs, 8-desmethylcoralyne (DMC), 5,6-dihydro-8-desmethylcoralyne (DHDMC), and palmatine, which differ in the chemical structures of their B- and/or D-rings. DNA topoisomerase-mediated cleavage assays revealed that these compounds were unable to poison mammalian type II topoisomerase. By contrast, the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
84
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 60 publications
(106 reference statements)
8
84
0
2
Order By: Relevance
“…Addition of counterions renders the double helices more flexible so the flow gradient becomes insufficient to orient the DNA molecules and thus the anisotropic CD pattern vanishes. It is to be noted that in special devices suitable to generate much higher hydrodynamic flow gradient (e.g., Couette flow cell), the DNA helices can be aligned even in the presence of salts and display very similar spectral pattern to that reported here [3,8,9].…”
Section: Resultssupporting
confidence: 63%
“…Addition of counterions renders the double helices more flexible so the flow gradient becomes insufficient to orient the DNA molecules and thus the anisotropic CD pattern vanishes. It is to be noted that in special devices suitable to generate much higher hydrodynamic flow gradient (e.g., Couette flow cell), the DNA helices can be aligned even in the presence of salts and display very similar spectral pattern to that reported here [3,8,9].…”
Section: Resultssupporting
confidence: 63%
“…Coralyne and its derivatives were shown to be inducers of topoisomerase I-DNA cleavable complexes, whereas the structurally similar benzophenanthridine alkaloid nitidine showed a dual poison activity for topoisomerases I and II (Pilch et al, 1997;Sanders et al, 1998;Makhey et al, 2000). In previous work from our laboratory, we have demonstrated that berberrubine has a potent activity as DNA topoisomerase II poison by stabilizing topoisomerase II-mediated cleavable complex in vitro .…”
mentioning
confidence: 86%
“…Unfortunately, depletion of the genomic DNA sample prevented us from obtaining the intervening sequences at the 5Ј end of the gene. We were, however, able to identify seven introns with lengths of 61,45,50,46,48,43, and 44 bp, whose locations are shown in Fig. 1A.…”
Section: Resultsmentioning
confidence: 88%
“…In contrast to the strong P. carinii topoisomerase I-poisoning activity obtained with the benzimidazoles and nogalamycin, no poisoning was seen with coralyne or nitidine (Fig. 6), both of which are potent human topoisomerase I poisons (26,46). Coralyne (and other protoberberines) are also inactive against both the A. nidulans and S. cerevisiae topoisomerase I enzymes (26,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation